Analisis Sarana dan Prasarana di KPA Kota Depok - Hafshah Noer Salsabillah; Christian Wiradendi Wolor; Eka Dewi Utari (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This research aims to analyze the availability and quality of facilities and infrastructure at the AIDS Prevention Commission (KPA) in Depok City. KPA, as the institution responsible for HIV/AIDS prevention and control, requires adequate facility support to optimize its performance. Based on observations and preliminary interviews, it was found that KPA Depok City has basic facilities such as a secretariat office, meeting rooms, and office equipment. However, there are still several constraints, including limited space for activities, lack of supporting equipment such as projectors and sound systems, and operational work equipment that is not available at each employee's desk. This research uses a survey method by distributing questionnaires to 25 KPA Depok City staff to get an initial picture of the condition of facilities and infrastructure. The results of this research are expected to serve as a basis for optimizing the use of existing resources and identifying development needs in the future, so that KPA Depok City can increase the effectiveness of its programs in HIV/AIDS prevention efforts.